2021
DOI: 10.35630/2199-885x/2021/11/1.9
|View full text |Cite
|
Sign up to set email alerts
|

Microelement Profile and Structure of Regionallymph Nodes During Senile Involution of Lymphoid Tissue

Abstract: The microelement profile and structure of lymph nodes were studied in experiment using old Wistar rats by means of a morphological method and the X-ray fluorescent analysis with synchrotron radiation. Their special qualitative and quantitative status is formed in regional lymph nodes that reflect age-related dynamics of lymphoid tissue. The content of trace elements and the size of compartments differ in lymph nodes of different localization. Age-related modifications in a microelement profile are characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Lymph nodes have great functional importance for the body, both in normal and pathological processes [ 33 , 34 , 35 ]. The lymph node plays a crucial role in the pathogenesis of inflammation [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lymph nodes have great functional importance for the body, both in normal and pathological processes [ 33 , 34 , 35 ]. The lymph node plays a crucial role in the pathogenesis of inflammation [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the lymphatic system in the pathology of internal organs and body systems is known; the authors found that the natural way to cleanse the focus of inflammation is regional lymphatic capillaries, vessels and lymph nodes, as well as its huge role in maintaining the constants of the internal environment [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The lymph node is a triedic homeostatic system including structural (lymphoid), hydration, and trace elements parts. These components allow to maintain lymph node workability in different periods of life [2]. The purpose of the study is to determine the intensity of age-induced changes of visceral lymph nodes including the structure, hydration and concentration of trace elements.…”
mentioning
confidence: 99%
“…We used the following a histological method, thermogravimetric method [3], X-ray fluorescence analysis using synchrotron radiation (RFA SI) [4] and statistical method using the StatPlus Pro 2009 program with determination of basic indicators. Results: The emergence of lymph theory of aging and concept of lymph region [1,2] poses the need to take into account changes in regional lymph node in aging. Not knowing what happens in organs and regional lymph nodes, we cannot consider agedependent changes (aging) in isolation.…”
mentioning
confidence: 99%
See 1 more Smart Citation